Promoting Collaborative Consultation to Improve the Quality of Inclusive Education in Indonesia - Sulaiman, Ahmad (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
Indonesia’s education sector has been experiencing development, but the inclusive segment needs more support since the number of disabled students are rising while the readiness of schools to nurture them seems underperformed. The main problem is the discrepancy between school educators’ competence and the special needs of students. In the west, it is common for school to have a collaborative consultation to overcome such problem. It interconnects collaborators in an equal position to reciprocally develop the best solution for existing problems. This paper aims to promote the term for education stakeholders in Indonesia.